Republic of Poland : Technical Note on Stress Testing the Banking Sector. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
This Technical Note discusses results of stress testing of the banking sector in Poland. The Polish banking system is well capitalized and liquid, as confirmed by stress tests results. Polish banks are, in aggregate, resilient even under severe adverse scenarios. Some small banks could fail to meet minimum regulatory capital and liquidity requirements in these scenarios, but with little impact on the overall banking system. Tests showed that only small banks, together representing up to 30 percent of the assets in the system, may have problems meeting the Basel III capital requirements in the recession scenarios.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet